Gambaran Tingkat Pengetahuan Mahasiswa Fakultas Kedokteran Gigi Universitas Trisakti Tentang Konsep Green Dentistry : Kajian pada Mahasiswa Program Studi Pendidikan Dokter Gigi semester 7(Laporan Penelitian) - Reinhart Christian Salim; Asyurati Asia (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Nowadays global warming has become the largest environmental problem as well as a threat to the world. Dentistry has contributed to a large amounts of waste like infectious waste, non infectious waste, radiographic waste, paper waste, and also the excesive use of electricity and water. Green Dentistry is a concept that refers to eco-friendly dental practice using improved technology and new innovations to decrease the amount of waste, toxic medical waste, pollution, and the over usage of electricity and water. The concept of Green Dentistry should be taught in the early stage of the dentistry student’s study period in order to ensure student’s capability in carrying out more eco-friendly dental procedure. Purpose: The purpose of this study is to obtain a general idea of the level of knowledge that is possesed by the Trisakti University Faculty of Dentistry Students’ of the Undergraduate Study program regarding the concept of Green Dentistry. Method: This study uses a descriptive observational, cross sectional method, using a questionnaire consisting of 14 questions about the knowledge on the concept of Green Dentistry. The total of respondents that are willing to participate in this study are 142, 7th Semester Students’ of the Undergraduate Study Program. Result: 28 students (19,71%) possess a good level of knowledge, 74 students (52,11%) possess an adequate level of knowledge, and the remaining 40 students (28,16%) possess a level of knowledge that is below average. Conclusion: The majority of students’ has an adequate level of knowledge regarding the concept of Green Dentistry.